2006
DOI: 10.1029/2006wr004885
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Holocene carbon accumulation in a western Siberian watershed mire using a three‐dimensional dynamic modeling approach

Abstract: [1] The vast undisturbed mires in western Siberia formed a significant sink of atmospheric carbon dioxide during the Holocene. However, the lack of spatially resolved simulation models hampers the quantification of Holocene carbon accumulation of the entire mire systems. Here we developed a three-dimensional dynamic model, based on a hydrological approach. We applied the model to a large mire complex in western Siberia to simulate its Holocene development and to quantify the long-term carbon accumulation rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…5 Zones C and D and Table 3). Borren and Bleuten (2006) modelled a LARCA range of 10-85 g C m −2 yr −1 (mean 16 g C m −2 yr −1 ) for a large mire complex in south-western Siberia, and our value falls within this range.…”
Section: Siberia (Zones C and D) And Far Eastern Russia (Zone E)mentioning
confidence: 93%
See 1 more Smart Citation
“…5 Zones C and D and Table 3). Borren and Bleuten (2006) modelled a LARCA range of 10-85 g C m −2 yr −1 (mean 16 g C m −2 yr −1 ) for a large mire complex in south-western Siberia, and our value falls within this range.…”
Section: Siberia (Zones C and D) And Far Eastern Russia (Zone E)mentioning
confidence: 93%
“…In a modelling study, Ise et al (2008) used a coupled physical-biogeochemical soil model at a site in northern Manitoba, Canada and found that peatlands could respond quickly to warming, losing labile soil organic carbon dur-ing dry periods. Similarly, Borren and Bleuten (2006), using a three-dimensional dynamic model with imposed artificial drainage to simulate the Bakchar bog in western Siberia, indicated that LARCA will drop from 16.2 to 5.2 g C m −2 yr −1 during the 21st century due to higher decomposition linked to reduced peat moisture content. Our simulations are based on climate forcing derived from the RCP8.5 scenario output from one Earth system model (HadGEM2-ES).…”
Section: Future Climate Impacts On Peatlandsmentioning
confidence: 99%
“…Also, we assumed that the extent of the peatland area is fixed, meaning that we do consider vertical growth of the peatland but not lateral expansion of the peatland. It is well known that lateral peatland expansion and the regional geographical context of peatlands strongly interact with peatland hydrology and development (Ingram 1982;Clymo 1984;Belyea and Baird 2006), but taking into account these aspects would require site-specific model parameterization (Borren and Bleuten 2006). The aim of this study, however, was to answer general questions and not to focus on site-specific properties.…”
Section: Model System and Study Approachmentioning
confidence: 99%
“…Hence, we modeled overland flow and drainage as water losses from the model. Lateral transport of water through the peat was described by Darcy's law (Rycroft et al 1975;Rietkerk et al 2004a;Borren and Bleuten 2006), meaning that lateral transport of water is driven by differences in hydraulic head.…”
Section: State Variable 3: Groundwater Tablementioning
confidence: 99%
“…The trend of the head gradient in the EW direction was almost constant over time (262 · 10 )7 ), indicating a steady flow in a western direction ( Figure 5). With a hydraulic conductivity of the 'plant layer' (that is, the active plant and litter layer in the hollows) of 548 m d )1 (Borren and Bleuten 2006) and thickness of the 'plant layer' of 0.5 m the average westward water flux was approximately 0.007 m 3 d )1 m )1 across the flow direction. The hydraulic gradient in the EW direction was not smooth.…”
Section: Patterns In Hydrologymentioning
confidence: 99%